Analisis Ciri Khas Busana Modern di Rowdra Dance Class sebagai Identitas Visual Komunitas Tari - Dwi Kinanti; Universitas Negeri Semarang (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of modern dance in Semarang City has spurred the emergence of various dance communities, each possessing distinct characteristics and visual identities. One community with a strong signature style is Rowdra Dance Class, which consistently blends modern and traditional elements in its costume designs. This study aims to describe the distinctive features of the modern costumes used by Rowdra Dance Class as the community's visual identity. A qualitative method with a descriptive approach was employed. Data collection involved in-depth interviews, observation, and documentation, with informants comprising the owner and dancers of Rowdra Dance Class. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the signature style of Rowdra Dance Class costumes lies in the fusion of modern and traditional elements, the use of bold and diverse colors, the incorporation of Indonesian ethnic motifs and accessories, and an aesthetic that is unique, luxurious, and distinctive. The consistent application of this costume concept makes Rowdra’s outfits easily recognizable and serves as a visual identity for the dance community. This study implies that costumes serve not merely as performance accessories but also as a medium for representing identity, character, and cultural values ​​within the performing arts community